KOMPETENSI GURU BK BERLATAR PENDIDIKAN BIMBINGAN KONSELING DAN NON PENDIDIKAN BIMBINGAN KONSELING - Akhir Pardamean; Ade Zahra Tifani; Anggi Hendriani; Nurul Hidayah; Tama Sentia Hasibuan (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The purpose of this research is to see the effectiveness of the counseling teacher in terms of the educational background of the counseling teacher. This is done because many counseling teachers have non-counseling education backgrounds. The type of research conducted is qualitive research, where the results of the research are stated in oral from. Data collection was carried out using literature studies. The results of this study are that counseling teachers who have a non-S1 counseling background are also able to provide effective counseling services for their counselees if the counseling teacher is willing to learn about the abilities that a counselor must have.